LECTURER PROFESSIONAL ENHANCEMENT IN MARITIME INSTITUTION: An Urgent Action - Sisca Cletus Lamatokan; Sopiah; May Vitha Rahmadhani (ASIAN PUBLISHER, 2022)
Lecturers are professionals in charge of planning and implementing the learning process, assessing results, conducting guidance and training as well as conducting research and community service. To achieve this performance, lecturers must be managed by higher education managers through the implementation of effective and efficient quality management in order to achieve the goals set by the institution. Professional lecturers at the Jakarta High School of Shipping Science are lecturers who come from practitioners, namely seafarers. To align the competence of academic lecturers with practitioners, it is necessary to carry out an improvement strategy that refers to policies and the need for increasing lecturer competence. This study uses a qualitative method with a case study approach. The sample used was taken based on purposive sampling technique. The findings and analysis show that the Maritime College as one of the maritime schools owned by the state has an adaptive competency improvement strategy in aligning the need for increasing lecturer competence based on the background of lecturers who come from seafarers and the need for adjustment of prospective lecturers to the requirements of lecturers according to legislation. applicable.